Cardiovascular Changes in Children with Acute Lower Respiratory Tract Infection - Kabir, Shahreen; Khatoon, Soofia; Fatmi, Lutful Ehsan; Banu, Nazneen Akhter; Mohiuddin, Arif Ahmed; Rana, Rubina Afroz (Bangladesh Journal of Child Health, 2019)
Background: Acute Lower Respiratory Tract Infections (ALRI), particularly Pneumonia and Bronchiolitis, are important causes of death in childhood in Bangladesh. The cardiovascular and respiratory systems function as a single unit and alteration in cardiorespiratory interactions, can cause significant changes in cardiac function. The objective of this study was to find out any electrical and functional changes, myocardial injury, frequency of heart failure and the outcomes in these patients with ALRIs. Methodology: It was a prospective observational study carried out at DMCH from January to June 2012 on 35 consecutive children admitted with ALRI, which were further diagnosed as pneumonia or bronchiolitis using operational definitions. Heart failure cases were identified and all the cases were then evaluated for any cardiovascular changes. Results: Most of the patients were male. ECG changes occurred in the form of tachycardia. Abnormal echocardiographic findings were noted in the form of pulmonary hypertension, left ventricular systolic (LV) dysfunction and tricuspid regurgitation. 82.9% had raised CK-MB and was significantly higher in patients with tachycardia and having abnormal echocardiographic changes. Nine patients developed heart failure, 3 of them had pulmonary hypertension along with LV systolic dysfunction and one of pulmonary hypertension and LV systolic dysfunction each. CK-MB was raised significantly in all the patients with heart failure. Conclusion: Raised CK-MB, tachycardia out of proportion on ECG and pulmonary hypertension with left ventricular systolic dysfunction were common findings in patients with ALRI. Bangladesh J Child Health 2019; VOL 43 (1) :27-34